Changing Course: Ideas, Politics, and the Soviet Withdrawal from Afghanistan - Sarah E. Mendelson (Princeton University Press, 2014)
THE "melancholy, long, withdrawing roar" that, as Matthew Arnold suggested, accompanies the collapse of empires has been heard recently from the East. In many ways, it began in Afghanistan—when the Soviet Union withdrew its troops in 1988 and 1989. Then the roar grew almost deafening as it rumbled through Eastern Europe in 1989 and 1990 and through the Baltic states, Ukraine, Moldova, the Trans-Caucusus, and the states of Central Asia in 1991. In the mid 1990s, its echo still reverberates as many in Russia, incredulous over events, speak of reassembling the empire.1 I came face to face with the "melancholy, long, withdrawing roar" of Soviet power in the course of researching this book, interviewing Soviet (and later, former Soviet) decision makers regarding the dramatic shifts in foreign policy that occurred in the 1980s. The puzzle for me was to understand how the new thinkers had won out over the old thinkers. I was particularly interested in the war in Afghanistan, and my reasons for wanting to meet these people were straightforward: these were the men who had run the war and who had gotten the withdrawal on the political agenda. By 1990, when I conducted most of the interviews in Moscow, glasnost had effectively broken down the barriers that had earlier prevented people from directly speaking or writing critically on the topic of the war in Afghanistan. New thinking in foreign policy had eroded the norm against discussing such topics with Westerners, especially with Americans. Nevertheless the war in Afghanistan, particularly after the withdrawal from Eastern Europe in 1989, remained a particularly sensitive issue for Soviets. The sentiments were not unlike those that surrounded the American war in Vietnam for American policymakers. Although the Soviet Union was less engaged in Afghanistan than the United States was in Vietnam, the aftermath of Afghanistan was even more dramatic. It was as if, following the U.S. withdrawal from Vietnam, first NATO and then the whole of the United States had collapsed. The subject of the war in Afghanistan was difficult to approach, both individually and collectively as a nation, but once confronted, it seemed just as difficult to set aside.